The Relationship Between Physical Activity and Quality of Life During the Confinement Induced by COVID-19 Outbreak: A Pilot Study in Tunisia - Slimani, Maamer; Paravlic, Armin; Mbarek, Faten; Bragazzi, Nicola L.; Tod, David (Frontiers in Psychology, 2020)
The present study aimed to determine the relationship between physical activity (PA) and quality of life (QoL) during the confinement caused by the COVID-19 outbreak. 216 participants (men: n = 112, women: n= 114) were included in the present study. They were divided into three groups (i.e., inactive group [IG]: less than 600 Metabolic Equivalent of Tasks (METs), n = 131; minimally active group [MAG]: from 600 to 2999 METs, n = 49; and health-enhancing PA group [HEPAG]: 3000 + METs, n = 36) based on their habitual PA level in the period of confinement. World Health Organization Quality of Life Instrument-Short Form (WHOQOL-Bref) and International Physical Activity Questionnaire-Bref (IPAQ-Bref) questionnaires were used to assess QoL and PA intensities. The main findings of the present study showed that MAG and HEPAG have better total PA, physical, psychological, social, and environmental QoL domains scores than IG (all, p<0.01). Small to large correlations (r ranging 0.14-0.72) were also observed between total PA, total walking activity, total moderate-intensity PA, total vigorous-intensity PA and QoL domains (all, p<0.01). PA with light- moderate- and vigorous intensities can be well recommended to decrease the negative psychosocial effect of confinement. However longitudinal studies are needed to draw causal inferences and underpin more robust and evidence-based and informed recommendations.